"Consulted to death": Personal stress as a major barrier to environmental co-management. (15th January 2020) - Young, Nathan; Cooke, Steven J.; Hinch, Scott G.; DiGiovanni, Celeste; Corriveau, Marianne; Fortin, Samuel; Nguyen, Vivian M.; Solås, Ann-Magnhild
Abstract: Co-management is widely seen as a way of improving environmental governance and empowering communities. When successful, co-management enhances the validity and legitimacy of decision-making, while providing stakeholders with influence over processes and outcomes that directly impact them. However, our research with participants in co-management across several cases leads us to argue that many of the individuals who contribute to co-management are subject to significant personal stress arising from both the logistical and social/emotional demands of participation in these processes. We argue that the literature on co-management has touched on this only indirectly, and that personal stress is a major challenge for participants that ought to be integrated into research agendas and addressed by policy-makers. In this article, we review the contours of the personal stress issue as it has appeared in our observations of co-management events and interviews with participants. While these findings are partial and preliminary, we argue that personal stress has theoretical and practical significance to the broader literature and process design. We conclude the article with recommendations for participants, researchers and policy-makers about how to consider and respond to problems of personal stress. Highlights: Co-management can cause personal stress among community-level participants. Stress is caused by costs, lack of support, conflict, and uncertainty. Scholars should incorporate individual-level variables into research agendas. Stress can be mitigated by providing resources and reforming processes.